Optimizing Coal Transportation Modes in Jambi Province: Strategic Decision-Making Using Integrated FAHP-Fuzzy TOPSIS - Firmansyah, Choiril; Sunitiyoso, Yos (International Journal of Economics Development Research (IJEDR), 2025)
The process of this research is to integrate the Fuzzy Analytic Hierarchy Process (FAHP) method and the Fuzzy Technique for Order Preference by Similarity to Ideal Solution (Fuzzy TOPSIS) by creating a strategic decision-making framework to optimize coal transportation modes in Jambi Province, Indonesia. An analysis of the inefficiency of coal transportation in Jambi was conducted due to the failure to achieve production targets, which were only 44-50% of the target set for 2022 and 2023.A thorough analysis has been conducted to determine both the criteria and sub-criteria for evaluating alternative coal transportation modes, starting from trucks using dedicated coal routes, combinations of trucks with dedicated coal trains, combinations of trucks with barges, and combinations of trucks with conveyors and barges. Underpinned by strong methodology controlling evaluation discrepancies and guaranteeing study validity, the approach included expert opinions from 25 stakeholders spanning government, industry, academia, and community sectors. Results reveal that at 38.5%, transportation costs are the most significant element; environmental impact follows at 27.3%; safety concerns at 19.8%; and time efficiency at 14.4%. Based on the analysis results, both through criteria weighing and testing against alternatives, it was found that the best mode of transportation is trucks using the special coal road. And it is recommended to consider the level of operational efficiency, reduction of environmental impact, and increasing regional competitiveness compared to other regions by selecting the most effective and strategic mode of transportation.